Squint-less arc array for near-field focusing in wideband systems. Issue 10 (3rd July 2021) - Kim, Sol; Kim, Jeong-Wook; Cho, Hyunyoung; Ahn, ByungKuon; Kim, Kwang-Seok; Yu, Jong-Won
Abstract : In this paper, the arc array for squint-less near-field focusing is used, theoretically analyzed, and verified. The arc array is designed to overcome the squint phenomenon in the near-field and transfers the maximum power at a focused distance. The implemented transmitter is composed of 16 × 1 vivaldi antennas with a 0.7 λ spacing and operates at a frequency of 5.8 GHz. In addition, the design method of the arc array is proposed, considering the focused distances. In the experiments, the bending degree of the arc array is 4.14 ∘ when the focused distance is 0.5 m. At a fractional bandwidth of 27.5%, the focus position is shifted 32%. On the other hand, in the arc array, the focus position is not shifted. Experimental results from the implemented arc array show good agreement with the proposed theory.